Globalization and Innovation in Emerging Markets - Gorodnichenko, Yuriy; Svejnar, Jan; Terrell, Katherine (2012)
Globalization brings opportunities and pressures for domestic firms in emerging markets to innovate and improve their competitive position. Using data on firms in 27 transition economies, the authors test for the effects of globalization through the impact of increased competition and foreign direct investment on domestic firms' efforts to innovate (raise their capability) by upgrading their technology, improving the quality of their product or service, or acquiring certification. They find that competition has a negative effect on innovation, especially for firms further from the efficiency frontier, and we do not find support for an inverted U effect of competition on innovation. The authors show that the supply chain of multinational enterprises and international trade are important channels for domestic firms' innovation. They detect no evidence that firms in a more pro-business environment are more likely to display a positive or inverted U relationship between competition and innovation, or that they are more sensitive to foreign presence.